Self esteem and locus of control in male substance dependents - Haider, Nighat; Asmat, Ali; Zafar, Salman; Dogar, Imtiaz Ahmad (Journal of Pakistan Psychiatric Society, 2020)
Objective: To find out levels of self esteem and locus of control among male drug dependent patients.Study Design: Cross sectionalPlace and duration of Study: The study was conducted in the department of Psychiatry and Behavioral Sciences, DHQ Hospital, Faisalabad in a duration of six months.Subjects and Methods: 100 male patients dependent on drugs from the inpatient facility of Model drug abuse and treatment center situated in the department of Psychiatry and Behavioral Sciences, DHQ Hospital, Faisalabad participated in this study through purposive convenient sampling technique. Rosenberg self esteem scale and Rotter’s Locus of control scale were administered to measure the levels of self esteem and locus of control. The results were obtained by using SPSS 17.Results: Descriptive statistics show that out of 100, 23 patients (23%) had low self esteem; the rest 77 (77%) fell into average category of self esteem. 24 patients (24 %) had internal locus of control while 76 (76 %) had external locus of control.Conclusion: The study showed that majority of participants had external locus of control while about one fourth participants had internal locus of control. Majority of the participants dependent on drugs had normal self esteem, about a quarter of the total sample had low self esteem.